Widgetry basics for i-Book - Shaarani, Ahmad Shaarizan; Kasmuri, Emaliana; Abd Manap, Nurulfajar; Karjanto, Juffrizal (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2014)
This teaching and learning series book provide guidance to create interactive book by using iBook Author. The emphasize of this book is to create the interactive book by adding text, graphics, movie, galleries, 3D objects and so on through widgets in the iBook Author.